Protests and Repression in New Democracies. Issue 1 (15th March 2017) - Aytaç, S. Erdem; Schiumerini, Luis; Stokes, Susan
Abstract : Elected governments sometimes deal with protests by authorizing the police to use less-lethal tools of repression: water cannons, tear gas, rubber bullets, and the like. When these tactics fail to end protests and instead spark larger, backlash movements, some governments reduce the level of violence but others increase it, causing widespread injuries and loss of life. We study three recent cases of governments in new democracies facing backlash movements. Their decision to scale up or scale back police repression reflected the governments' levels of electoral security. Secure governments with relatively unmovable majorities behind them feel freer to apply harsh measures. Less secure governments, those with volatile electoral support, contemplate that their hold on power might weaken should they inflict very harsh treatment on protesters; they have strong incentives to back down. Our original survey research and interviews with civilian authorities, police officials, and protest organizers in Turkey, Brazil, and Ukraine allow us to evaluate this explanation as well as a number of rival accounts. Our findings imply that elected governments that rest on very stable bases of support may be tempted to deploy tactics more commonly associated with authoritarian politics.